2003
DOI: 10.1007/s00122-003-1518-3
|View full text |Cite
|
Sign up to set email alerts
|

Wheat puroindolines interact to form friabilin and control wheat grain hardness

Abstract: Wheat grain is sold based upon several physiochemical characteristics, one of the most important being grain texture. Grain texture in wheat directly affects many end use qualities such as milling yield, break flour yield, and starch damage. The hardness (Ha) locus located on the short arm of chromosome 5D is known to control grain hardness in wheat. This locus contains the puroindoline A ( pina) and puroindoline B ( pinb) genes. All wheats to date that have mutations in pina or pinb are hard textured, while w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(141 citation statements)
references
References 33 publications
(50 reference statements)
9
127
1
Order By: Relevance
“…Transgenic studies in rice , wheat (Beecher et al 2002;Martin et al 2006), and corn (Zhang et al 2009) have demonstrated that Pin mutations are causative to hard grain texture. PINA and PINB are not functionally interchangeable and control grain hardness via cooperative binding to starch granules (Hogg et al 2004;Swan et al 2006;Wanjugi et al 2007a;Feiz et al 2009b). PIN binding to starch granules is mediated by polar lipids (Greenblatt et al 1995) and PIN abundance is correlated with seed polar lipid content (Feiz et al 2009b).…”
mentioning
confidence: 99%
“…Transgenic studies in rice , wheat (Beecher et al 2002;Martin et al 2006), and corn (Zhang et al 2009) have demonstrated that Pin mutations are causative to hard grain texture. PINA and PINB are not functionally interchangeable and control grain hardness via cooperative binding to starch granules (Hogg et al 2004;Swan et al 2006;Wanjugi et al 2007a;Feiz et al 2009b). PIN binding to starch granules is mediated by polar lipids (Greenblatt et al 1995) and PIN abundance is correlated with seed polar lipid content (Feiz et al 2009b).…”
mentioning
confidence: 99%
“…A quence for both pin-a and pin-b are soft in texture, whereas, wheats that have mutations in pin-a and or pin-b are hard textured (Hogg et al 2004). …”
mentioning
confidence: 99%
“…However, the evidence that grain hardness reduces grain breakage during pearling is meaningful for barley breeders, since a major genetic factor controlling grain hardness has recently been revealed as the genotype of hordoindoline (Hinb2) 2,22 which was the homoeologous of "friabilin" in wheat 5,6,13,18 . An effective breeding strategy to reduce the broken-grain rate as a major quality problem for two-rowed pearling barley is the use of Hinb2b allele, which hardens the endosperm texture.…”
Section: Factors Influencing the Quality Characteristicsmentioning
confidence: 99%